2015
DOI: 10.1007/s00436-015-4360-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome stress responses in Schistosoma mansoni

Abstract: The proteasome proteolytic system is the major ATP-dependent protease in eukaryotic cells responsible for intracellular protein turnover. Schistosoma mansoni has been reported to contain an ubiquitin-proteasome proteolytic pathway, and many studies have suggested a biological role of proteasomes in the development of this parasite. Additionally, evidence has suggested diversity in proteasome composition under several cellular conditions, and this might contribute to the regulation of its function in this paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…In previous studies, these primers had been used to verify the expression of the transcripts in adult S . mansoni worms incubated with CUR [38, 39]. To confirm the specificities of the primers, the PCR products were sequenced in the ABI 3100 automated sequencer (Applied Biosystems) by using a Dye Terminator kit.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, these primers had been used to verify the expression of the transcripts in adult S . mansoni worms incubated with CUR [38, 39]. To confirm the specificities of the primers, the PCR products were sequenced in the ABI 3100 automated sequencer (Applied Biosystems) by using a Dye Terminator kit.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, our data suggest that under the inhibition caused by MG-132, treated parasites are engaged in the recovery of the proteasome function through the synthesis of new proteasome units. Similarly, De Paula et al [ 62 ] showed that different types of stress could drastically up-regulate the expression of two proteasome genes, namely SmHul5 and SmUbp6, suggesting that the proteasome is important in the cellular stress response in this parasite.…”
Section: Discussionmentioning
confidence: 89%
“…The proteasome is involved in the biogenesis of EVs [ 66 ] and also controls protein homeostasis and degradation of damaged proteins [ 67 ]. Furthermore, in schistosomes, the proteasome plays an important role in the cellular stress response and survival of the parasite [ 68 ]; it has been shown that treating mice with a proteasome inhibitor prior to infection with S. mansoni cercariae significantly impaired parasite development [ 69 ] and in vitro treatment of schistosomula with siRNAs targeting a deubiquitinase subunit of the 19S regulatory particle significantly reduced parasite viability [ 70 ].…”
Section: Discussionmentioning
confidence: 99%